ANALISIS MANAJEMEN ENERGI AKIBAT ALIH FUNGSI RUANGAN PADA MASA PANDEMI DI RSD MANGUSADA BADUNG - I Made Deny Setiawan; I Gede Dyana Arjana; Cok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2022)
In 2020 as a result of the Covid-19 pandemic, the number of patients at the Mangusada Hospital continued to increase. The increasing number of patients has led to a change in the function of the room in handling special patients with Covid-19. The change in the function of the room will certainly have an impact on changes in electrical energy consumption. The results showed that the measurement of light intensity and room temperature in Building C of RSD Mangusada did not meet the standards of the Minister of Health Regulation No. 7 of 2019. The factor causing the non-fulfillment of light intensity was because many lights had dimmed and died and in the air system the standards were not met due to performance. AC that is not optimal in cooling the room but is still used if this continues will be a waste of energy. Energy saving efforts can be applied to the lighting system by replacing TL-D lamps with 36watt power consumption, 2850 lumens with LED tube type EM/ Mains T8 lamps, power consumption of 18.2 watts, 2900 lumens where energy savings are obtained by 49.4% or budget savings of Rp. 134,514,169,-